1973
DOI: 10.1021/j100907a017
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies of the adsorption of sulfur-containing gases at 423.deg.K on porus adsorbents. I. Adsorption of hydrogen sulfide, methanethiol, ethanethiol, and dimethyl sulfide on silica gels

Abstract: Calorimetric heats of adsorption have been determined at coverages up to one-tenth of a monolayer for hydrogen sulfide, methanethiol, ethanethiol, and dimethyl sulfide, adsorbed at 423°K on silica gels of varying surface hydroxyl group concentrations. Adsorption isotherms have been determined and entropies of adsorption calculated to provide additional data on the nature of the adsorbed species. The high values of the initial heats of adsorption of up to 30 kcal mol-1 are associated with surface heterogeneity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…10 Only few data about adsorption capacities of these compounds on silica−alumina gels have been published. Glass et al 11 compared the adsorption of several sulfur compounds on silica gels and found a correlation between the loadings and the number of surface silanol groups. Steuten et al 12 investigated the adsorption of organic and inorganic sulfur compounds from methane on a silica−alumina gel and a zeolite at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…10 Only few data about adsorption capacities of these compounds on silica−alumina gels have been published. Glass et al 11 compared the adsorption of several sulfur compounds on silica gels and found a correlation between the loadings and the number of surface silanol groups. Steuten et al 12 investigated the adsorption of organic and inorganic sulfur compounds from methane on a silica−alumina gel and a zeolite at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the adsorption of sulfur dioxide on a range of metal oxides and gelatinous oxides Ross, 1971, 1972a,b) have provided information on heats of adsorption below monolayer coverage and possible mechanisms for the formation of the adsorbed complex. These studies had both basic and technological implications and were later extended (Glass and Ross, 1973) to include determinations of entropies of adsorption of other sulfur-containing gases which often occur as atmospheric pollutants-hydrogen sulfide, organic thiols, and disulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on magnesia (lo), alumina (17), and silica (24) yielded values of 80, 20 t o 50, and < 10 kcal mol-' for the heats of adsorption at surface coverages of 1 pmol mP2 in this temperature range. The alumina heat values were clearly related t o the 'previous history' of the samples and the decrease in the heats over the oxide set was related to the decrease in ionicity of the oxides and to their ability t o form compounds with sulfur dioxide.…”
Section: Discussionmentioning
confidence: 76%
“…The calorimeter was operated in the adiabatic mode and the heat measurement conditions were adapted from those used by Smith and Ford (15) as recently reported (11). Entropies of adsorption were calculated from classical thermodynamic equations (16,17).…”
mentioning
confidence: 99%